Pathology of pulmonary tuberculosis: has the tiger changed it’s stripes? - Desai, Heena Maulek; Vaideeswar, Pradeep; Gaikwad, Manish; Amonkar, Gayathri Prashant (Autopsy and Case Reports, 2022)
Background: India accounts for the highest number of TB cases globally (almost one-fifth of the global burden and almost two-thirds of the cases in South East Asia. Furthermore, the development of drug resistance of varying levels such as multi-drug resistant TB (MDR-TB), extensively-drug resistance TB (XDR-TB) and total-drug resistant TB (TDR-TB) has been on the increase, and now India also features in the 27 high-MDRTB-burden countries. Almost parallel to these developments, in the last few years, we have been encountering less common morphological forms of pulmonary TB (PTB) at autopsies. With these less common manifestations of the disease, we undertook this study to examine the changing trends in the morphological pattern of pulmonary TB over the recent years.Methods: In this 3-year retrospective study, adult autopsy cases of PTB (that significantly contributed to the final cause of death) were studied in detail. HIV-positive cases were excluded from the study. The clinical details, gross appearances of the pulmonary lesions, microscopic pattern and Ziehl-Neelsen (ZN) staining were studied. Extrapulmonary involvement and causes of death were documented.Results: Pulmonary tuberculosis as a cause of death at autopsy was seen in 130 adult patients over 3 years. The age range was between 12 to 70 years. Anti-tuberculous therapy had been administered in 33 of them, but only one patient had taken complete therapy. Dyspnea was the commonest respiratory symptom seen in 51 cases (39.2%). Tuberculous bronchopneumonia was the commonest lesion (45.3%), miliary lesions (including localized miliary) accounted for 26% while fibrocavitary lesions (including the ones not involving apex) were seen in 13% cases. Other morphologies included nodular forms of TB (13%), localized miliary lesions (11.9%), and fibrocavitary lesions, not necessarily involving the apex (11.7% of all fibrocavitary cases), and predominant pleuritis with underlying lung involvement by TB in 1 case. Many cases of TB bronchopneumonia had a bronchocentric pattern of distribution (14.7%). On microscopy, caseating granulomas were seen in 93% cases, only caseation necrosis was seen in 4.6% cases, and necrotizing granulomas with abscess-like reaction in 11.5% cases. ZN staining was positive in 92 cases (70.7%). All the extrapulmonary lesions showed caseating granulomas histologically. The final cause of death was found to be primarily tuberculous in 106 cases (81.5%), whereas in 24 cases (19.5%) pulmonary TB was attributed to the secondary cause of death.Conclusion: The typical apical involvement of secondary TB was not seen in most of our cases. This could indicate a difference in the morphology and the pattern of lung involvement in recent years. The difference in gross morphology does not affect the pattern of involvement of the lung. In our study, we have observed both; a change in morphology, i.e., more cases of TB bronchopneumonia, and a change in the pattern of involvement like nodular forms, localized miliary forms, and fibrocavitary lesions not necessarily involving the apex. We postulate that this less common manifestation of pulmonary TB is closely related to the development of multi-drug and microbial resistance posing serious medical challenges.